2009
DOI: 10.1590/s0021-75572009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre ventilação mandatória intermitente e ventilação mandatória intermitente sincronizada com pressão de suporte em crianças

Abstract: Objective: To compare intermittent mandatory ventilation (IMV) with synchronized intermittent mandatory ventilation plus pressure support (SIMV+PS) in terms of time on mechanical ventilation, duration of weaning and length of stay in a pediatric intensive care unit (PICU). Methods:This was a randomized clinical trial that enrolled children aged 28 days to 4 years who were admitted to a PICU between October of 2005 and June of 2007 and put on mechanical ventilation (MV) for more than 48 hours.These patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…One randomised study found no difference between weaning with PSV, VC, or without a protocol [634]. Another study that included 70 children found that the duration of MV did not differ, regardless of whether PCV or SIMV with PSV was used [670]. A pilot study showed that the use of NAVA accelerates the weaning process [671].…”
Section: Weaning Strategiesmentioning
confidence: 99%
“…One randomised study found no difference between weaning with PSV, VC, or without a protocol [634]. Another study that included 70 children found that the duration of MV did not differ, regardless of whether PCV or SIMV with PSV was used [670]. A pilot study showed that the use of NAVA accelerates the weaning process [671].…”
Section: Weaning Strategiesmentioning
confidence: 99%